Seeds of Maya Development: The “Fiestas y Ferias de Semillas” Movement in Yucatan (Alternautas, 2022)
This article describes the fiestas y ferias de semillas movement that take place in the Yucatan region, in Mexico, and offers an interpretation that stresses its importance not just as a site of Indigenous resistance, but as a strategic opportunity for the construction of alternatives to development. Celebrated in different sub-regions of this culturally distinctive area, these events bring together Maya-speaking peasants, anti-GMO activists, and organic produce aficionados from the federal states of Campeche, Quintana Roo and Yucatan. Here, Maya understandings of welfare and prosperity are historically and politically reconfigured within a Pan-Yucatec Maya cultural perspective, at the same time leaning on and leading to what I call Cosmayapolitan ways of locating communities and social actors in the global situation.